A ludicidade como instrumento facilitador da leitura no 2º ano do ensino fundamental - PINHEIRO, Odábias dos Passos (2019)
This paper presents the results of a research highlighting relevant points about the use of playfulness as a facilitating tool in the reading process in elementary school. The ideas presented here are based on authors such as Vigotsky (1987, 1998 and 2001), Piaget (1996 and 1997). Morais (2012), Freire (2007), Ferreiro (2004) and others emphasize the importance of playfulness to train student readers. The research emphasizes how important it is to use playfulness in classroom practices. It deals with a reflection on authors about the process of knowledge construction during the period of training and learning, as well as the transformations that occur in the present time. The study allowed us to understand how the reflection must be in the life of this professional. Developed through bibliographical readings of qualitative nature and field observations, however, moving towards a better understanding of the social phenomenon in which the elementary school is inserted. In this way the research makes a concept of playfulness as well as the historical rescue of the traditional methodologies to the present ones in the process of teaching learning. It discusses the pedagogical role that playfulness should have in elementary school, based on pedagogical practice and teacher training that is extremely important, highlighting how it relates to teaching and playing. Emphasizing that all care should happen in a playful and dynamic way so that the child can achieve integral and social development in their learning process. The results of the research point out the importance of professionals working with quality for the training of student readers.